THE EFFECT OF THE ADDITION OF SURIMI FISH CATFISH DUMBO (Clarias gariepinus) ON THE QUALITY OF THE FISH NUGGET - Sari, N. Ira; ', Firmansyah; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was aimed to determine the effect of the number of catfish surimi added on the quality of the fish nuggets. The study used experiment method with completely randomized design, consisting of a 5 level of the treatment, those were N0 (adding with minced fish meat 500 g), N1 (adding with surimi 500 g), N2 (adding with surimi 475 g), N3 (adding with surimi 450 g), and N4 (adding with surimi 425 g). The results showed that addition of 500 g African catfish surimi produced the best quality of the nugget, indicated by: the appearance tidy, clean, and a brownish yellow color; the taste of fish flavored); the aroma of fish quite noticeably; and the texture was solid, very compact, and chewy. It contained moisture 55.19%, protein 16.04%, fat 7.77% and ash 1.97%.Keyword: catfish, surimi, nugget.